Survey and Identification of Fusarium Head Blight Pathogens of Wheat in the Western Cape Region of South Africa - Ali Al-Hashimi; Augustine Innalegwu Daniel; Omolola Aina; Morné Du Plessis; Marshall Keyster; Ashwil Klein (Pathogens)
Fusarium head blight (FHB) is a major disease affecting wheat production worldwide, caused by multiple Fusarium species. In this study, seven Fusarium strains were isolated from wheat fields across the Western Cape region of South Africa and identified through phylogenetic analysis. The strains were classified into three species complexes: the Fusarium graminearum species complex (FGSC), Fusarium incarnatum-equiseti species complex (FIESC), and Fusarium tricinctum species complex (FTSC). Disease severity was highest in the South coast regions of Swellendam (42.73%) and Caledon (38.00%), with the dough stage of wheat development showing the highest disease rate (0.3 in Swellendam and Caledon). The phylogenetic analysis showed distinct clustering of these isolates with known species from the NCBI database, confirming their classification. F. ipomoeae was uniquely found in Swellendam and Caledon, while F. tricinctum occurred only in Klipheuwel and Caledon, highlighting geographical variation in species distribution. Mycotoxin profiling revealed that F. culmorum and F. pseudograminearum produced zearalenone, F. culmorum and F. tricinctum produced 15-acetyl-deoxynivalenol (15-ADON), while F. pseudograminearum produced nivalenol (NIV). These findings provide significant insights into the distribution of Fusarium species and their associated trichothecene chemotypes in the Western Cape, which is crucial for developing effective FHB management strategies and ensuring food security and safety.